Hubungan Aktivitas Fisik dengan Fleksibilitas Otot Hamstring pada Anak Usia 9-12 Tahun di SD Negeri 4 Pemecutan - Ni Putu Preti; Indah Pramita; Gede Parta Kinandana; I Putu Gde Surya Adhitya (KOLONI, 2026)
Hamstring muscle flexibility is an important component of children’s physical fitness that may be influenced by physical activity. Low physical activity and increased sedentary behavior among elementary school children may reduce muscle elasticity, including hamstring flexibility. This study aimed to determine the relationship between physical activity and hamstring muscle flexibility in children aged 9-12 years at SD Negeri 4 Pemecutan. This study used an analytical observational design with a cross-sectional approach. A total of 95 respondents were selected using purposive sampling. Physical activity was measured using the Physical Activity Questionnaire for Older Children (PAQ-C), while hamstring flexibility was measured using the Sit and Reach Test. Data were analyzed descriptively and bivariately using the Spearman rho test. The results showed that most respondents had a moderate level of physical activity, with 60 respondents (63.2%). Hamstring flexibility was mostly categorized as good, with 25 respondents (26.3%). The Spearman rho test showed a p-value of 0.251 (p > 0.05) with a correlation coefficient of r = 0.119. In conclusion, there was no significant relationship between physical activity and hamstring muscle flexibility in children aged 9-12 years at SD Negeri 4 Pemecutan. The positive correlation indicated that higher physical activity tended to be associated with better hamstring flexibility, although the relationship was very weak.